Study of Making Pear Peel Extract Lotion (Pyrus Bretschneideri) as an Antioxidant - Muhammad, Syaifullah; Lestari, Indah Tri; Afifah, Syarifah Nur; Putri, Embun Fatimah Azzahra; Rosmalia AR, Latifah; Jumadi, Jumadi (Journal of Patchouli and Essential Oil Products, 2023)
The skin of the  pear (pyrus bretschneideri) contains f  lavonoid compounds which are efficacious as antioxidants,  which are able to inhibit or prevent oxidation of the substrate caused by free radicals. Pear peel extract can  be used as a repellent or antioxidant so that it can be developed into an antioxidant lotion. To maintain the stability of pear peel extract in the form of lotions, it is necessary to formulate appropriate lotions. The purpose of this study was to find out the lotion formulation of the active ingredient oleum rosae to find out the results of the evaluation carried out on the pear peel extract lotion. The method used is experimental using 6 lotion formulations with a concentration of pear peel extract of 3 and 4%, vitamin C variations of 2, 4, and 6%. The results of the lotion from pear peel extract were evaluated for 1 week. Ephysical quality valuation includes organoleptic test, pH test, vit amin C content test. From the results of the study, lotions with the formulation F4 are the best preparations, namely a slightly viscous dosage form, soft texture, white color, oleum rosae fragrance, homogeneous, stable at pH 6 and dispersion power 5-7 cm. The conclusion of the study is that pear peel extract can be made lotion preparations with a wide variety of concentration variations. Keywords: lotion, pear peel (Pyrus bretschneideri), physical quality